How do you solve 7x - 10= - 6x ^ { 2}?

2 Answers
Sep 22, 2017

Use the quadratic formula.

Explanation:

First, rearrange the equation to match the form ax^2 + bx + c = 0

6x^2 + 7x - 10 = 0

a= 6
b = 7
c = -10

Then using the quadratic formula: x = (-b+-sqrt(b^2 - 4ac))/(2a)
Substitute in the numbers:

x = (-7+-sqrt(7^2 - 4(6*-10)))/(2*6)

and simplify:

x = (-7+-sqrt(289))/(12)

x = (-7+-17)/(12)

So your two solutions would be:

x = 5/6 and x = -2

Sep 22, 2017

7x-10=-6x^2

6x^2+7x-10=0

6x^2+12x-5x-10=0

6x*(x+2)-5*(x+2)=0

(6x-5)*(x+2)=0

Hence x_1=5/6 and x_2=-2

Explanation:

1) I transferred squared term to left side.

2) I decomposed polynomial using common multiplier.

3) I solved each multiplier.